PEMAKAIAN KONJUNGSI DALAM NOVEL SALI: KISAH SEORANG WANITA SUKU DANI - Sitti Mariati (Balai Bahasa Provinsi Papua, 2019)
Conjunction have function to connect two or more language elements. Conjunction as one of means to achieve cohesiveness a discourse, including novel as a discourse prose. As do in the novel Sali: Kisah Seorang Wanita Suku Dani, the author uses conjunctions to connect the word with the word, phrase by phrase, clause by clause, and sentence by sentence so as to create a cohesive meaning. Continuum meaning that contained in the novel Sali: Kisah Seorang Wanita Suku Dani, and its conjunction as a causal relation with conjunctions sebab, karena, and maka; relation of conflict with conjunctions tetapi and namun; relation of exceptions or ekseptif with conjunction kecuali; relation of konsesif with conjunction meskipun; relation of purpose with conjunction supaya; relation of addition or additive with conjunctions dan, juga, and serta; relation of choice or alternative with conjunction atau; relation of sequence or sekuensial with conjunction kemudian; relation of time with conjunction setelah; relation of terms with conjunction apabila, and relation of manner in conjunction dengan.